2023
DOI: 10.1021/acsomega.2c06893
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Density Functional Theory Approaches for Desulfurization of Dibenzothiophene from Diesel Fuel with Imidazole-Based Heteropolyacid Catalysts

Abstract: Oxidative desulfurization (ODS) has been proved to be an efficient strategy for the removal of aromatic sulfur compounds from diesel oils, which are one of the main sources of air pollution. Heteropolyacid catalysts are highly active species for ODS, but the promotion of their catalytic activity and clarification of their catalytic mechanism remain an important issue. Herein, a series of novel imidazole-based heteropolyacid catalysts are prepared by a one-pot method for multiphase deep ODS of fuel with hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…For instance, Ren et al synthesized 1-vinylimidazol-based HPAs with H 5 PMo 10 V 2 O 40 using the one-pot method and applied them to the ODS process of DBT model oil. The results showed that the desulfurization rate of DBT reached 99.9%, and the HPAs were able to maintain for desulfurization rate of 97.7% after being recycled 7 times . Wang et al immobilized H 3 PW 12 O 40 (HPW) onto the surface of a MWW (Mobil composition of matter 22) zeolite for the ODS of petroleum fractions, specifically straight-run gasoline (SRG) and fluid catalytic cracking (FCC) gasoline.…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ren et al synthesized 1-vinylimidazol-based HPAs with H 5 PMo 10 V 2 O 40 using the one-pot method and applied them to the ODS process of DBT model oil. The results showed that the desulfurization rate of DBT reached 99.9%, and the HPAs were able to maintain for desulfurization rate of 97.7% after being recycled 7 times . Wang et al immobilized H 3 PW 12 O 40 (HPW) onto the surface of a MWW (Mobil composition of matter 22) zeolite for the ODS of petroleum fractions, specifically straight-run gasoline (SRG) and fluid catalytic cracking (FCC) gasoline.…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
“…The results show that S compounds were removed from both the model diesel and real diesel samples using moderate experimental conditions (50 °C and H 2 O 2 /S ratio of 6). 69 Wang et al prepared a series of composite materials consisting of vanadium-substituted Keggin-type polyoxometalates anchored on amine-functionalized Ce-MCM-41 and evaluated for its catalytic activity in ODS of 2000 ppm of DBT model fuel using molecular oxygen as an oxidant. Wang et al found that substitution of V into the Keggin framework of phosphotungstic acid (PTA) has a positive impact on the ODS process, and the conversion of DBT is improved with increasing the V-substituted amount of POM (Table 3).…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%